2001
DOI: 10.1182/blood.v97.8.2323
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor–induced angiogenesis in vivo requires specific cleavage of fibrillar type I collagen

Abstract: The contribution of specific type I collagen remodeling in angiogenesis was studied in vivo using a quantitative chick embryo assay that measures new blood vessel growth into well-defined fibrillar collagen implants. In response to a combination of basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), a strong angiogenic response was observed, coincident with invasion into the collagen implants of activated fibroblasts, monocytes, heterophils, and endothelial cells. The angiogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
120
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 52 publications
(79 reference statements)
8
120
0
2
Order By: Relevance
“…Therefore, no underlying mechanism has been proposed to explain why neutrophil MMP-9 might function as a critical proangiogenic protease. Previously, we used a quantitative angiogenesis model in the chicken embryo (28) and demonstrated that avian inflammatory cells and their MMPs, including monocyte MMP-13 and heterophil MMP-9, were critical for the induction of both physiologic and tumor angiogenesis (30,31). By taking advantage of this system, which allows for direct access to the angiogenic site and testing of intact viable cells and their delivered products, we directly analyzed for the involvement of functioning human neutrophils and the catalytic capabilities of their MMP-9 in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no underlying mechanism has been proposed to explain why neutrophil MMP-9 might function as a critical proangiogenic protease. Previously, we used a quantitative angiogenesis model in the chicken embryo (28) and demonstrated that avian inflammatory cells and their MMPs, including monocyte MMP-13 and heterophil MMP-9, were critical for the induction of both physiologic and tumor angiogenesis (30,31). By taking advantage of this system, which allows for direct access to the angiogenic site and testing of intact viable cells and their delivered products, we directly analyzed for the involvement of functioning human neutrophils and the catalytic capabilities of their MMP-9 in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated the functional role of distinct inflammatory cells and their MMPs during physiologic and tumorinduced angiogenesis by using a quantitative in vivo angiogenesis model (28), modified from the original assay described by Folkman and colleagues (29). In the model, angiogenesis is induced in 3D collagen rafts grafted on the chorioallantoic membrane (CAM) of the developing chicken embryo.…”
mentioning
confidence: 99%
“…56 In addition to this, TIMP-1, -2 and -3 have all been shown to inhibit EC migration and invasion in type I collagen gel assays. 52,57 The repeated observations of a correlation between MMP inhibition and reduced tumor angiogenesis provide strong evidence for the involvement of the MMPs in this process. However, they do not provide specific information about which particular MMPs may be involved as these inhibitors are broad-range, often with not all of their targets clearly defined.…”
Section: Endogenous Inhibitors Of Metalloproteinasesmentioning
confidence: 97%
“…Col(I) turnover is important for correct alignment of sprouting endothelial cells. 18,28 Whereas its digestion allows elongation of vascular tubes, the level of Col(I) synthesis can limit neovascularization, because it contributes to the development of the matrix on which the vascular tube and vascular smooth muscle cells extend. [36][37][38] Halofuginone can exert an inhibitory effect on these various aspects of angiogenesis, as has been demonstrated in different experimental settings.…”
Section: Discussionmentioning
confidence: 99%
“…Because halofuginone has been reported to influence angiogenesis 18 and because Col(I) remodeling is important for blood vessel sprouting and formation of endothelial tubular structures, [26][27][28] we assessed development of the angiogenic vasculature in halofuginone-treated and control pig skin. Immunohistochemical analysis of CD31-positive endothelial cells in normal skin from control and halofuginone-treated piglets did not reveal differences in vascular density (75 6 5 and 75 6 13 vessels/mm 2 , respectively).…”
Section: Halofuginone Attenuates Angiogenesis During Melanoma Developmentioning
confidence: 99%